Indonesia-South Korea Security Cooperation: Progress, Problems, and Possibilities in Defence Diplomacy - Kenzie Sultan Ryvantya (JURNAL HUBUNGAN LUAR NEGERI, 2024)
Though far from public spotlight relative to economic and socio-cultural aspects, Indonesia and South Korea maintain intense and mutually-beneficial cooperation in security affairs. As middle powers, both countries share aligned views on regional and global peace and security with ample capacity to play more influential roles. This article seeks to describe how Indonesia and South Korea uphold cooperation in security through conducting defence diplomacy, which is the usage of armed forces and other related defence infrastructure to advance a state’s diplomatic agenda through peaceful, non-violent means. Findings show that since bilateral relations was upgraded to a strategic partnership in 2006 until 2023, Indonesia and South Korea has made significant progress in three fields: aerospace and naval defence industry cooperation, strategic communications and consultations, and joint military exercises and security exchanges. However, issues in financing, technology transfer, and geopolitical dynamics have caused obstructions in those fields. Furthermore, several avenues of cooperation may be explored further and deeper in the future, including in maritime security, cybersecurity, counter-terrorism, and multilateral engagement.